2013
DOI: 10.1042/bj20121753
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and pathological roles of mitochondrial SLC25 carriers

Abstract: The mitochondrion relies on compartmentalization of certain enzymes, ions and metabolites for the sake of efficient metabolism. In order to fulfil its activities, a myriad of carriers are properly expressed, targeted and folded in the inner mitochondrial membrane. Among these carriers, the six-transmembrane-helix mitochondrial SLC25 (solute carrier family 25) proteins facilitate transport of solutes with disparate chemical identities across the inner mitochondrial membrane. Although their proper function reple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 221 publications
(286 reference statements)
2
87
0
Order By: Relevance
“…Citrate is generated in the mitochondria, but it is an important substrate for biosynthesis in the cytosol upstream of IDH1 (23). As a mitochondrial citrate carrier (CIC), SLC25A1 promotes the efflux of citrate from mitochondria into the cytosol (24)(25)(26), where it can be converted into oxaloacetate and acetyl-CoA by ATP citrate lyase (ACL) or into isocitrate by aconitase 1 (Aco1) and then oxidized by IDH1 to generate NADPH and α-KG. Both acetyl-CoA and NADPH are the substrates for lipid biosynthesis, which is critical for cell proliferation, and therefore, SLC25A1 is an important molecule upstream of IDH1.…”
Section: Discussionmentioning
confidence: 99%
“…Citrate is generated in the mitochondria, but it is an important substrate for biosynthesis in the cytosol upstream of IDH1 (23). As a mitochondrial citrate carrier (CIC), SLC25A1 promotes the efflux of citrate from mitochondria into the cytosol (24)(25)(26), where it can be converted into oxaloacetate and acetyl-CoA by ATP citrate lyase (ACL) or into isocitrate by aconitase 1 (Aco1) and then oxidized by IDH1 to generate NADPH and α-KG. Both acetyl-CoA and NADPH are the substrates for lipid biosynthesis, which is critical for cell proliferation, and therefore, SLC25A1 is an important molecule upstream of IDH1.…”
Section: Discussionmentioning
confidence: 99%
“…The high homology existing between SLC25A33 and SLC25A36 has suggested that these two members of the MCF might have similar functions (1,2). However, the substrate(s) transported by SLC25A36 has not yet been discovered, and its function is still completely elusive.…”
mentioning
confidence: 99%
“…The human genome harbors as many as 53 SLC25 genes encoding a superfamily of transport proteins called solute carrier 25 (SLC25) 3 family or mitochondrial carrier family (MCF) (1,2). The members of this family are characterized by three tandem repeated sequences of ϳ100 amino acids, each folded into two transmembrane ␣-helices and containing a distinct signature motif (PROSITE PS50920, PFAM PF00153, and IPR00193).…”
mentioning
confidence: 99%
“…The mitochondrial carrier system ( MCS ) (“see glossary”) transports small molecules between mitochondria and the cytoplasm, thereby regulating the function of both compartments [13]. In mammals, the MCS comprises the transporters of the 53 member canonical SLC25A family and a lesser number of identified non-canonical transporters.…”
Section: The Mitochondrial Carrier Systemmentioning
confidence: 99%
“…This is significant because understanding the systems-level function of the MCS may provide new opportunities for therapeutic metabolic reprogramming. For detailed coverage of the history of mitochondrial carrier research, the reader is referred to several excellent review articles [13, 24, 25]. …”
Section: The Mitochondrial Carrier Systemmentioning
confidence: 99%